1983
DOI: 10.1126/science.6612330
|View full text |Cite
|
Sign up to set email alerts
|

RCapillaries: Basement Membrane Thickening by Galactosemia Prevented with Aldose Reductase Inhibitor

Abstract: A twofold thickening of capillary basement membranes of rat retinas resulting from dietary galactose was prevented by sorbinil, an inhibitor of aldose reductase. Since the basement membrane thickening was ultrastructurally similar to that typical of diabetic retinopathy, it may indicate changes in vessel permeability and susceptibility to hemorrhage. Galactosemic rats should be useful models for studying basement membrane-related complications of diabetes and for examining the potential biochemical regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
89
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(95 citation statements)
references
References 13 publications
6
89
0
Order By: Relevance
“…Hyperglycaemiainduced mitochondrial production of ROS has been shown to induce activation of the polyol pathway [20]. Inhibition of aldose reductase activity has previously been used to inhibit glucose metabolism through the polyol pathway [21,22,23]. In the present study we used AL-1576, which in comparative studies with other aldose reductase inhibitors has been shown to be both highly potent and selective and to lack antioxidant effects [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemiainduced mitochondrial production of ROS has been shown to induce activation of the polyol pathway [20]. Inhibition of aldose reductase activity has previously been used to inhibit glucose metabolism through the polyol pathway [21,22,23]. In the present study we used AL-1576, which in comparative studies with other aldose reductase inhibitors has been shown to be both highly potent and selective and to lack antioxidant effects [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion may in agreement with the Mizutani et al report [36] , which stated that selective Müller cell functional abnormalities in early stage of the development of diabetic retinopathy, and with the report of Dubois et al [37] , who found Müller cells death causes retinal dysplasia, photoreceptor apopotosis, and finally retinal degeneration and proliferation of the retinal pigment epithelium. Another reason that reinforce the concept of retinal degeneration by sorbitol pathway is the protection or delaying of diabetic retinopathy by using aldose reductase inhibitor (tolrestat) in diabetic rats [14] , prevention of glomerular disease by aldose reductase inhibitor (sorbinil) in diabetic rats [38] , correcting corneal endothelial changes in diabetic patient by topical aldose reductase inhibitor (placebo) in diabetic patients [39] , Prevention of diabetic complications and nerve tissue by aldose reductase inhibitors (sorbinil or sulindac) in rats lens [40] , prevention of diabetic retinopathy by aldose reductase inhibitor (sorbinil) in diabetic patients [41] , and prevention of basement membrane thickening by aldose reductase inhibitor (sorbinil) in retina of galactosemic rats [3] .…”
Section: Discussionmentioning
confidence: 99%
“…It causes an array of long-term systemic complications [1] . Among these complications is the diabetic retinopathy, which characterized by the increase in capillary permeability [2] , thickening of the basement membrane [3,4] , pericyte necrosis followed by the capillary occlusion, microaneurysms, endothelial cell proliferation, haemorrhage, oedema, neovascularization [5,6] and lately, a fibrous or glial tissue often grows with the vessels to a degree that traction and distortion of the retina may occur, producing retinal damage and retinal detachment [7] and resulting in blindness [8] .…”
Section: Introductionmentioning
confidence: 99%
“…These cells accumulate them because of their poor penetration across the membranes. These abnormal metabolic results have been reported to be factors responsible for diabetic complications such as cataracts (11), retinopathy (12), neuropathy (13), and nephropathy (14). Therefore, ALR2 inhibitors have considerable potential for the treatment of these diseases.…”
Section: Introductionmentioning
confidence: 99%